2016
DOI: 10.1038/nmat4553
|View full text |Cite
|
Sign up to set email alerts
|

Organically linked iron oxide nanoparticle supercrystals with exceptional isotropic mechanical properties

Abstract: It is commonly accepted that the combination of the anisotropic shape and nanoscale dimensions of the mineral constituents of natural biological composites underlies their superior mechanical properties when compared to those of their rather weak mineral and organic constituents. Here, we show that the self-assembly of nearly spherical iron oxide nanoparticles in supercrystals linked together by a thermally induced crosslinking reaction of oleic acid molecules leads to a nanocomposite with exceptional bending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
236
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(254 citation statements)
references
References 32 publications
18
236
0
Order By: Relevance
“…Figure a–c and Figure S2 demonstrate that spin‐coating results in ordered assemblies of iron oxide NCs. We crosslinked the ligands of adjacent NCs by using the heat treatment reported by Dreyer et al . The crosslinking process is performed by heating the NC assembly to 350 °C for 30 minutes and is illustrated in Figure d,e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a–c and Figure S2 demonstrate that spin‐coating results in ordered assemblies of iron oxide NCs. We crosslinked the ligands of adjacent NCs by using the heat treatment reported by Dreyer et al . The crosslinking process is performed by heating the NC assembly to 350 °C for 30 minutes and is illustrated in Figure d,e.…”
Section: Resultsmentioning
confidence: 99%
“…The crosslinking process is performed by heating the NC assembly to 350 °C for 30 minutes and is illustrated in Figure d,e. The crosslinking process binds two adjacent ligands together by splitting the C=C double bond of the OA molecule into saturated C−C single bonds (Scheme ) . This effectively exchanges the weak van der Waals interactions between neighboring ligands with strong covalent bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Our understanding of nanocrystal superlattice mechanical behavior would also be enriched by obtaining a full, tensile stress-strain curve for this material, to understand properties such as strength and fracture toughness, and by studying the time dependence of superlattice mechanical properties. To accomplish these goals, it is desirable to fabricate selfassembled nanocrystal arrays with bulk length scales, which remains a challenge in the field (8,12,49). Nevertheless, selfassembled nanocrystal superlattices are a rich model system for understanding mechanical behavior in materials under nanoscale confinement, and the properties of polymer nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…This is all the more remarkable because mechanical cohesion in the superlattices is attributed to van der Waals interactions between ligands on neighboring nanocrystals (10,11), which are weak enough that the ligands are liquid at room temperature when not attached to nanocrystals. Superlattice strength and stiffness can be further elevated to values that are unprecedented for polymer nanocomposites by cross-linking the organic ligands that coat the nanocrystals (12). The unusual combination of physical properties in nanocrystal superlattices presents intriguing opportunities to use these materials as mechanically actuated optoelectronic sensors (13,14), lightweight solar sails (15), and ultrathin barriers and coatings (16,17), but warrants the development of a thorough understanding of the mechanical behavior of nanocrystal superlattices.…”
mentioning
confidence: 99%
“…Another recent study conducted by Greiner et al () demonstrated for the first time that 31.93 ± 0.97 nm pores present within endogenous collagen Type I fibers are sufficient to induce the osteogenic differentiation of human stem cells. A collagen‐like scaffold which mimics the collagen pore structures was developed by self‐assembly of silicon dioxide (SiO 2 ) nanoparticles linked together by a thermally induced crosslinking reaction of oleic acid molecules (Dreyer et al, ). The obtained substrates showed pore size of 34 ± 14 nm that directly leads to the successful osteogenic differentiation of adult neural crest‐derived inferior turbinate stem cells (ITSCs).…”
Section: Nanoporesmentioning
confidence: 99%